Numerical simulation of initial mixing of marine wastewater discharge from multiport diffusers. Issue 7 (30th September 2014) - Xue, Wanyun; Huai, Wenxin; Qian, Zhongdong; Yang, Zhonghua; Zeng, Yuhong
Abstract : Purpose: – The purpose of this paper is to examine the initial mixing of wastewater discharged from submerged outfall diffusers and the influence of port configurations on wastewater distribution based on computational results. Design/methodology/approach: – Marine wastewater discharges from multiport diffusers are investigated by numerically solving three-dimensional and uncompressible two-phase flow fields. A mixture model simulates this flow and the standard k-e model to resolve flow turbulence; inter-phase interactions were described in terms of relative slip velocity between phases. Computations were performed for two values of the port spacings s/H with different current Froude numbers F. Findings: – Computational results compared well with previous laboratory measurements. Numerical results reveal that for both the closely spaced (s/H=0.21) and widely spaced (s/H=3.0) ports, the normalized dilution Sn becomes independent of F; further, the length of the near field xn and the spreading layer thickness hn are functions of F. For the closely spaced ports, the wastewater discharge behaves like a line plume, the Coanda effect is obvious, quasi-bifurcation is present, horseshoe structures of the jets in the planes are rapidly produced and then squashed and elongated, and the jet trajectories based on maximum velocity precede those based on maximum concentration. For the widely spaced ports, the wastewater discharge behaves like a point plume, the Coanda effect is not obvious, bifurcation is present, horseshoe structures of the jets in the planes are gradually produced and become ellipses, and the jet trajectories based on maximum velocity are similar to those based on maximum concentration. Originality/value: – Semi-empirical equations are presented to predict major near field characteristics. These provide guidance for designing multiport diffusers and assessing environmental impact.